2022
DOI: 10.53730/ijhs.v6ns2.5656
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malocclusion and orthodontic treatment need among 15 year old school children of rural Central India

Abstract: Objective: To assess the prevalence of malocclusion and orthodontic treatment need among the rural school going 15‑years-old children Materials and Methods: A descriptive cross sectional study was carried out among 400 school going children in the central part of India. Occlusal features such as overjet, overbite, crossbite, crowding, and spacing were documented using a structured proforma and the need for orthodontic treatment was evaluated using the index of orthodontic treatment need dental health component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this study, out of 900 students had 80.6% of any form of malocclusion, which is in close proximity to the findings of Noor et al (2021) 11 who observed a frequency of malocclusion in 75% of sample size in Abbottabad. Similarly, Chauhan et al (2022) 9 , who observed a prevalence of malocclusion in 71% of students in the age group of 15 years school going children in Bangalore, India. Mangat et al (2020) 8 conducted a survey in Hungary on 483 schools going children aged 16-18 years and detected 70.4% frequency of malocclusion in the sample.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study, out of 900 students had 80.6% of any form of malocclusion, which is in close proximity to the findings of Noor et al (2021) 11 who observed a frequency of malocclusion in 75% of sample size in Abbottabad. Similarly, Chauhan et al (2022) 9 , who observed a prevalence of malocclusion in 71% of students in the age group of 15 years school going children in Bangalore, India. Mangat et al (2020) 8 conducted a survey in Hungary on 483 schools going children aged 16-18 years and detected 70.4% frequency of malocclusion in the sample.…”
Section: Discussionmentioning
confidence: 83%
“…2 Mangat et al (2020) 8 conducted a survey in Hungary on 483 schools going children aged 16-18 years and detected 70.4% frequency of malocclusion in the sample. Chauhan et al (2022) 9 , who observed a prevalence of malocclusion in 71% of students in the age group of 15 years school going children in Bangalore, India. Amaral et al (2020) 10 assessed the degree of malocclusion and the requirement for orthodontic management in Indian young people between the ages of 16 and 24.…”
Section: Introductionmentioning
confidence: 99%
“…Malocclusion is one of the most common dental problems that has an increasing prevalence (1)(2)(3)(4)(5)(6)(7) It may cause many ailing effects such as poor esthetics, functional limitations, speech defects as well as increase in the prevalence of dental caries and periodontal disease (8)(9)(10)(11)(12)(13) . Occlusion has also a significant influence on how individuals perceive and evaluate other individuals (14,15) .…”
Section: Introductionmentioning
confidence: 99%
“…Figure(1) Comparison of the responses between males and females regarding if they had taken orthodontic treatment or not…”
mentioning
confidence: 99%